Herding Behavior in the Indian Stock Market : An Empirical Study - Gupta, Pooja; Kohli, Bindya (Indian Journal of Finance, 2021)
The herding behavior in financial markets indicates the process whereby the different participants of the market trade in a similar direction simultaneously. This kind of trading pattern seems like a consensus in the market. There are different reasons for herding to exist : to be part of a group, to avoid the feeling of being left out, reaction to some kind of new information, etc. In this paper, we tried to identify the existence of herding behavior in the Indian stock market. The markets were examined over a time frame of the last 15 years to determine the existence of herding behavior at various points of time. The three time periods selected for the study were 2003 – 2007 (pre - financial crisis), 2008 – 2012 (sub-prime crisis), and 2013 – 2017 (post) crisis. The study used security return dispersion as a substitute for herd behavior. In order to test the presence of herding behavior, linear regression model using dummy variables was used. The evidence supported the presence of herding in the Indian stock market during the financial crisis time period and the post-crisis period. In the pre - financial crisis period, there was no herding phenomenon observed.